Anti-Cycle-Slip LDPC Decoding Algorithm for BPSK System - Dazhong Wu; Haidong Wu (Dianxin kexue, 2014)
When cycle-slip occurs in BPSK modulation system, sign of information sequence which is input of LDPC decoder is opposite to the original one. This problem will lead to decoder failure. Anti-cycle-slip LDPC decoding algorithm based on belief propagation was proposed. Modified algorithm modifies initial likelihood ratio information according to information between check nodes and variable nodes by an iterative decoding computation. Modified algorithm can eliminate the influence of cycle-slip and ensure normal function of LDPC decoder. Simulation result shows that modified decoding algorithm has the same performance with traditional decoding algorithm without cycle-slip, which means that the modification of initial likelihood ratio doesn't lead to decoding performance loss. When cycle-slip happens, traditional decoding algorithm fails. Decoding LDPC of odd check node degree by anti-cycle-slip algorithm will overcome the impact of cycle-slip totally. Modified algorithm has the same decoding performance no mater cycle-slip happens.